Papusza / Bronisława Wajs. Tears of Blood : A Poet's Witness Account of the Nazi Genocide of Roma - Bartash, Volha,; Kamusella, Tomasz,; Shapoval, Viktor, (Roma History and Culture ;, 2024)
Ratfale Jasfa (Romani: 'Tears of Blood') is a poem by the Romani poet Papusza (Bronisława Wajs) who survived the German occupation and the Second World War in Volhynia, currently Ukraine. It is also one of the earliest known testimonies by a Romani genocide survivor and a Romani woman. This book introduces the recently re-discovered manuscript which is four times longer than the previously known text. The volume includes a transcript of the poem in Romani, a translation into English, extensive historical-philological commentaries, alongside stand-alone chapters on the poet, manuscript and the historical context.